0134 Reviewing the impact of a one-day fully immersive simulation faculty development course. (2nd November 2015) - Bidwai, Anita; Mercer, Simon
Abstract : Background/context: Faculty development is critical to the success of any simulation program. 1 The Centre for Simulation and Patient Safety (CSPS) has designed a one-day course for participants interested in developing teaching and facilitation skills in high fidelity simulation. This involved 'hands on' workshops on mannequin set up, control, scenario facilitation and design. This formed the start of a 'hub-and-spoke' model for supporting faculty development. Methodology: To review the impact of the course on the participants, we devised a questionnaire. This was emailed to 60 participants who attended 4 courses between July 2013 and October 2014. Questions reviewed motivation to attend and their simulation experience after the course. We also investigated why participants hadn't pursued their interest. Results/outcomes: 24/60 participants replied to the questionnaire. 13/24 were Anaesthetists, 9/24 were Consultants. 15/24 attended the course with the intention of teaching simulation at CSPS. 9/24 intended to develop skills and teaching of simulation within their own hospital. Since attending the course only 15/24 have taught on simulation courses, 10/15 have taught at CSPS. Those who have taught at CSPS have taught 3 times or less. 78% stated difficulties due to work commitments and would be encouraged to develop their skills if they had 'greater support', 'further exposure to simulation' and 'regular updates'. Conclusions and recommendations: Despite attending a one-day faculty development course many have found it difficult to continue their interest due to work/time restrictions and requirements to attend other courses. This could be overcome by allowing fully immersive simulation instruction sessions to be included in clinician's job plans. Participants developing simulation within their own hospital have taken advantage of the 'hub-and-spoke' model offered by CSPS as part of their faculty development program. Reference: Waxman KT, Telles CL. The use of Benner's framework in high-fidelity simulation faculty development: The Bay Area Simulation Collaborative model. Clin Simulat Nurs. 2009;5:e231–e235